Oral push-pull osmotic pumps of pentazocine hydrochloride: Development and evaluation - Mishra B.; Makesh B.; Sankar C. (My University, 2025)
The present study was aimed to formulate and evaluate oral osmotic pumps of pentazocine HCl that are expected to deliver the drug as solution for prolonged period of time with reduced frequency of drug administration and reduced side effects. Push-Pull osmotic pumps of pentazocine HCl were prepared using different formulation variables like diameter of pores, presence of surfactant in formulation core, addition of osmopolymer pectin and presence/absence of water-soluble polymer (carboxymethylcellulose sodium). Fabricated osmotic pumps were evaluated for weight variation, coating thickness, pore diameter, drug content and in vitro release studies. Release rates were found to be independent of size of pores, agitation intensity, and pH of the release medium. The presence of surfactant, water-soluble polymer and osmopolymer (pectin) affected the drug release significantly. Almost all the osmotic pumps gave controlled and prolonged drug release profiles beyond 2 h of lag phase.